2019
DOI: 10.1016/j.cegh.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge towards Zika among medical students, interns and general practitioners in Indonesia: A cross-sectional study in Aceh

Abstract: Background: The aim of this study was to assess the level of knowledge towards Zika among medical students, medical interns and general practitioners (GPs) in Indonesia. Methods: A cross-sectional study was conducted in Aceh province of Indonesia in 2016. A set of validated questionnaire, consisting 24 questions, was used to assess the knowledge. Logistic regression was used to estimate the differences in knowledge between groups. Results: A total of 1031 participants were included in the final analysis in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…For instance, Zika was not listed in the 2006 National General Practitioner Competence List of the Republic of Indonesia [68]. Therefore, while a few medical schools in Indonesia have incorporated the subject into their curriculum, this knowledge is not a mandatory subject for medical doctor graduates in Indonesia [69]. In addition, we found no independent factor that was significantly associated with knowledge among GPs.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, Zika was not listed in the 2006 National General Practitioner Competence List of the Republic of Indonesia [68]. Therefore, while a few medical schools in Indonesia have incorporated the subject into their curriculum, this knowledge is not a mandatory subject for medical doctor graduates in Indonesia [69]. In addition, we found no independent factor that was significantly associated with knowledge among GPs.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, there are some studies conducted that addressed this issue [9,[15][16][17][18][19]. One of which was conducted among dentists in India [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study surveyed practitioners from different countries revealed that the majority of participants have an inadequate knowledge regarding ZIKV [17]. However, a recent study conducted among general practitioners (GPs) in Indonesia showed that 64% of them had good knowledge regarding ZIKV [18]. In addition, another recent study conducted among GPs in Indonesia showed that 66.5% of them had a good knowledge of pregnancy-related issues of ZIKV [19].…”
Section: Discussionmentioning
confidence: 99%
“…Zika virus infections have affected Southeast Asian countries, such as Indonesia [15], Singapore [16], Vietnam [17], and Thailand [18], and Microcephaly, associated with Zika infection [19], has been also reported in Southeast Asian countries. Previous literature has furthered the knowledge, attitude, practice, and vigilance of healthcare professionals from Malaysia and some Southeast Asian countries [20,21,22,23,24,25]. However preparedness and response studies among healthcare professionals is still lacking in Malaysia and other Southeast Asian countries.…”
Section: Introductionmentioning
confidence: 99%